Zakah for Asnaf Al-Gharimun in Brunei Darussalam: Concepts and Practices - Abdullah, Rose; Haqqi, Abdurrahman Raden Aji (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2017)
This research paper discusses the concepts of debt in Islam in relation to the category of al-gharimun that entitle for receive zakah. The data from the authority department has shown an alarming increase in number of applicant for zakah under the category of asnaf Al-Gharimun. Why was the number increased and who are actually eligible to receive zakah under the category of Al-Gharimun? This paper tries to answer these questions. The concept of debt in al-Qur’an will be discussed and various discussions by Islamic scholars and researchers will be analysed. Data gathered from several officers of Islamic Religious Council of Brunei Darussalam through personal interviews. The phenomenon was due to misunderstanding and ignorant among the public with regards to what kind of debts that are eligible under the category of Al-Gharimun to receive zakahDOI: 10.15408/aiq.v9i2.5092